The meaning between writing and reception - Bendebla Djelloul, Ben Smain Smail (Pegem Journal of Education and Instruction, 2026)
Problems relating to meaning, productionand reception are among the most importantissues to be resolved, and there is no doubt thatthe process of interpretation can only be achieved through the cooperation of writing